BOOK REVIEW OF ROALD DAHL’S GEORGE’S MARVELLOUSE MEDICINE - Wega, Laurensius (LANTERN (Journal on English Language, Culture and Literature), 2016)
Novel is a long printed story about imaginary character and events. George’s Marvelouse Medicine is novel for children. This novel is easy to understand and written in trivial language because it used to introduce children about literary. There is some of picture to describe the look of the character and what characters do in some occasion to keep the reader interest in reading. It was a good novel but there is something in the ending that makes it a little akward. The ending is hanging and it’s feels like there is something unfinished like the story are having more potential to be continued. masih berpotensi supaya cerita dilanjutkan dan dapat menghasilkan akhir cerita yang lebih baik. Kelemahan berikutnya adalah kurangnya peringatan kepada pembaca karna didalam novel tersebut terdapat banyak bahan-bahan yang berbahaya jika dikonsumsi. Karena novel ini ditujukan kepada anak-anak maka diharapkan adanya tambahan peringatan kepada mereka untuk tidak meniru dan memakan bahan bahan yang ada dalam cerita novel ini.